Clinical outcome of treatment with serine-threonine kinase inhibitors in recurrent epithelial ovarian cancer: a systematic review of literature - Ciccone, Marcia A. (Expert Opin Investig Drugs, 2016)
INTRODUCTION: While serine-threonine kinases (STK) are attractive therapeutic targets in epithelial ovarian cancer, clinical outcomes of STK inhibitors in the management of recurrent disease have not been completely described. AREAS COVERED: A systematic literature review of published clinical studies on STK inhibitors targeting mTOR, MAPK, and aurora kinase pathways in recurrent epithelial ovarian cancer was conducted, revealing 18 clinical trials (497 patients). Pooled analyses were performed to assess treatment response, survival time, and adverse events. Median progression-free survival was 3.4 months in STK inhibitor-based therapy, and the average response rate and clinical benefit rate were 13% and 67%, respectively. Among regimens comprised of only STK inhibitors (11 trials, 299 patients), median progression-free time was 2.7 months, response rate was 10%, and clinical benefit rate was 64%. Compared to single STK inhibitor monotherapy (52.5%), clinical benefit rates significantly improved when STK inhibitors were combined with a cytotoxic agent (71.4%), other class biological agent (74.2%), or an additional STK inhibitor (95.0%) (all, P ≤ 0.002). EXPERT OPINION: STK inhibitor-based therapy showed modest activity for recurrent epithelial ovarian cancer with reasonable clinical benefit rates, suggesting its potential utility for maintaining disease stability if supported by future studies. Efficacy appears greatly improved in appropriately selected patient populations, especially those with low-grade serous ovarian carcinoma, platinum-sensitive disease, cancers with somatic RAS or BRAF mutations, and when used in a combination regimen with a cytotoxic or biological agent.